Nano anti-corrosion waterproof coating capable of resisting high temperature, low temperature, acid and alkali
By using modified nanosilicon dioxide, the problems of nanoparticles agglomeration and uneven dispersion are solved, and the mechanical properties and weather resistance of nanocoatings are significantly improved.
Patent Information
- Application Number
- CN202411801634.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-07
AI Technical Summary
Nanoparticles are prone to agglomeration and uneven dispersion in the base material, resulting in low nanocoating performance.
Modified nanosilica is used to form hydrogen bonds with the nanosilica surface through dielectric esters and/or diols as modifiers, improving the dispersion and mechanical properties of nanosilica.
It improves the mechanical properties of nanocoatings, including strength, toughness, wear resistance, etc., and at the same time enhances the acid and alkali resistance, waterproofing and light-resisting properties of the coating.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coatings, and in particular to a nanometer anticorrosive and waterproof coating that is resistant to high and low temperatures and is acid and alkali resistant. Background Art
[0002] Paint is composed of base material, filler, additives and water. Currently commonly used base materials include alkyd, epoxy, aliphatic polyurethane, pure acrylic emulsion, inorganic silicates, organic-inorganic composites, etc. Fillers are divided into two types: inorganic fillers and organic fillers. Commonly used additives include dispersants, thickeners, defoaming agents, etc.
[0003] With the continuous advancement of new materials and technologies, people's requirements for coatings are getting higher and higher. Traditional coatings have poor scrub resistance. After a period of use, the surface will become mottled. Based on the above problems of traditional coatings, nano coatings came into being. Nano coatings are a type of coating with certain special functions obtained by using nanoparticles in coatings. They have excellent scrub resistance, suspension stability and thixotropy, and are non-toxic, harmless and odorless, opening up great space for the development of coatings.
[0004] Although nano coatings have many advantages and are a new type of high-performance coatings, there are still certain problems that need to be solved, such as the agglomeration of nanoparticles and the uneven dispersion of nanoparticles in the base material. If these problems can be solved, the performance of nano coatings will reach a higher level. Summary of the invention
[0005] The present invention provides a nanometer anticorrosive and waterproof coating that is resistant to high and low temperatures and acid and alkali, which solves the problem in the related art that nanometer particles are easy to agglomerate and are unevenly dispersed in a base material, resulting in low performance of the nanometer coating.
[0006] The technical solution of the present invention is as follows: A nano-anticorrosive and waterproof coating that is resistant to high and low temperatures and acid and alkali comprises the following raw materials in parts by mass: 30-40 parts of pure acrylic emulsion, 10-20 parts of modified nano-silicon dioxide, 2-4 parts of nano-titanium dioxide, 3-6 parts of nano-zinc oxide, 2-4.4 parts of additives, and 5-9 parts of water, wherein the modified nano-silicon dioxide is nano-silicon dioxide modified by a modifier, and the modifier comprises a dibasic ester and / or a diol.
[0007] In the present invention, the dibasic ester may be any one or more dibasic esters, and the diol may be any one or more diols.
[0008] As a further technical solution, the mass ratio of the modifier to the nano-silicon dioxide is 0.05~2:20.
[0009] As a further technical solution, the mass ratio of the modifier to the nano-silicon dioxide is 0.1~1:20.
[0010] The present invention limits the mass ratio of the modifier to the nano silicon dioxide to 0.1-1:20, thereby further improving the mechanical properties of the nano coating.
[0011] As a further technical solution, the modifier includes a dibasic ester and a diol in a mass ratio of 1:9 to 4:1.
[0012] The present invention uses dibasic ester and diol in a mass ratio of 1:9 to 4:1 as modifiers, further improving the mechanical properties of the nano coating. The reason may be that the dibasic ester has good affinity with the pure acrylic emulsion, and the residual hydroxyl group of the diol can form a hydrogen bond with the pure acrylic emulsion. Although the bond energy of a single hydrogen bond is weak, the combination of multiple hydrogen bonds can obtain a very considerable bonding strength. Therefore, when the dibasic ester and the diol are combined with modified nano silicon dioxide, the mechanical properties of the obtained nano coating are better.
[0013] As a further technical solution, the modifier includes a dibasic ester and a diol in a mass ratio of 1:4 to 2:3.
[0014] The inventors have experimentally found that when the mass ratio of dibasic ester to diol is 1:4 to 2:3, the mechanical properties of the nano coating are further improved.
[0015] As a further technical solution, the dibasic ester includes dicyclohexyl phthalate.
[0016] As a further technical solution, the diol includes one or two of 2,5-di-tert-butylhydroquinone and 4,4'-dihydroxybiphenyl, preferably 4,4'-dihydroxybiphenyl.
[0017] The present invention limits 4,4'-dihydroxybiphenyl as the diol, thereby further improving the mechanical properties of the nano coating.
[0018] As a further technical solution, the preparation method of the modified nano-silicon dioxide comprises the following steps: dissolving the modifier in a solvent, adding the nano-silicon dioxide for modification, and drying to obtain the modified nano-silicon dioxide.
[0019] As a further technical solution, the modification includes a first modification and a second modification in sequence, the first modification time is 30~50min, and the second modification time is 20~40min; the first modification process is accompanied by high-speed stirring, and the speed of the high-speed stirring is 3000~5000r / min, and the second modification process is accompanied by low-speed stirring, and the speed of the low-speed stirring is 200~300r / min.
[0020] As a further technical solution, the solvent includes one or more of ethanol, acetone, and ethyl acetate.
[0021] The preparation method of modified nano-silica in the present invention can make the nano-silica have a good modification effect, because the interaction force between the hydrogen bonds that aggregate on the surface of the nano-silica is not strong, and they can be separated under the shear force of high-speed stirring at a rotation speed of 3000-5000 r / min, and then the hydrogen bonds will be rapidly reorganized when stirring at a low speed of 200-300 r / min. During the reorganization process, the hydroxyl groups on the surface of the nano-silica will form hydrogen bonds with the dibasic ester and / or diol to achieve a good modification effect.
[0022] As a further technical solution, the auxiliary agent includes the following components in parts by weight: 0.5-1 part of dispersant, 0.1-0.3 part of wetting agent, 0.2-0.6 part of defoaming agent, 0.3-0.6 part of film-forming auxiliary agent, 0.2-0.5 part of antifreeze agent, 0.5-1 part of thickener, and 0.2-0.4 part of pH regulator.
[0023] In the present invention, dispersants, wetting agents, defoamers, film-forming aids, antifreeze agents, thickeners and pH regulators are added as auxiliary agents, and the dispersants, wetting agents, defoamers, film-forming aids, antifreeze agents, thickeners and pH regulators can all be conventional components in the art.
[0024] Dispersants can be distributed in a directional manner on the surface of solid particles, relying on charge repulsion to keep pigments and filler particles in a dispersed and suspended state for a long time in the coating system; wetting agents can significantly reduce the surface tension of the liquid and the interfacial tension between the liquid phase and the solid phase, allowing the liquid phase and solid particles to be fully wetted, shortening the dispersion time of pigments and fillers; thickeners can significantly increase the viscosity of the coating, change the rheological properties of the coating, and help the coating system to be stable for a long time. When used in combination with other additives, the provided coating has excellent performance.
[0025] The working principle and beneficial effects of the present invention are: 1. The present invention provides a nano coating, comprising pure acrylic emulsion, modified nano silicon dioxide, nano titanium dioxide, nano zinc oxide, additives and water, wherein the modified nano silicon dioxide is nano silicon dioxide modified by dibasic ester and / or diol. By using pure acrylic emulsion as a base material, the nano coating is provided with good adhesion, acid and alkali corrosion resistance, weather resistance, gloss retention and color retention. The addition of modified nano silicon dioxide improves the mechanical properties of the coating, including strength, toughness, wear resistance, etc. At the same time, the addition of nano titanium dioxide can shield ultraviolet rays and improve the aging resistance and antibacterial properties of the coating. The addition of nano zinc oxide ensures the waterproof effect and weather resistance of the coating. Water, as the basic solvent of the coating, can effectively mix other raw materials. The obtained nano coating has excellent properties, is not only resistant to high and low temperatures, acid and alkali, but also has a good waterproof effect.
[0026] 2. The nano-silicon dioxide modified by dibasic ester and / or diol is added in the present invention to improve the mechanical properties of the nano-coating. The reason is that: the hydroxyl groups on the surface of the nano-silicon dioxide can form hydrogen bonds with the dibasic ester and / or diol, thereby achieving the effect of modification. After the surface of the nano-silicon dioxide is modified, the agglomeration of the nano-silicon dioxide can be reduced, and the dispersibility in the base material can be improved, thereby achieving the effect of improving the mechanical properties of the nano-coating. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] The parameters of the raw materials in the following examples and comparative examples are as follows: The pure acrylic emulsion was pure acrylic emulsion PA242, purchased from Anhui Zhongen Chemical Co., Ltd.; The hydroxyethyl cellulose is Dow hydroxyethyl cellulose QP100MH; Nano-silicon dioxide is XFI03 nano-silicon dioxide with a specific surface area of 156.16m 2 / g, particle size 20nm, purchased from Jiangsu Xianfeng Nanomaterial Technology Co., Ltd.; Nano titanium dioxide is TTP-A16 anatase nano titanium dioxide with a specific surface area of 60m 2 / g, particle size 10nm, purchased from Jiangsu Tianxing New Materials Co., Ltd.; The particle size of nano zinc oxide is 20nm; The dispersant is dispersant 5040; The wetting agent is wetting agent X-405; The defoamer was Dow Corning DC-65 water-based silicone defoamer; The film-forming aid is lauryl alcohol ester; The antifreeze is ethylene glycol; The pH adjuster is pH adjuster AMP-95.
[0029] Example 1 S1. Dissolve 0.05 parts of dicyclohexyl phthalate in 50 parts of acetone, add 20 parts of nano-silicon dioxide, stir at 3000 r / min for 50 min, stir at 200 r / min for 40 min, and dry to obtain modified nano-silicon dioxide; S2. Evenly mix 40 parts of pure acrylic emulsion, 20 parts of modified nano silicon dioxide, 4 parts of nano titanium dioxide, 6 parts of nano zinc oxide, 1 part of dispersant, 0.3 parts of wetting agent, 0.6 parts of defoaming agent, 0.6 parts of film-forming aid, 0.5 parts of antifreeze agent, 1 part of hydroxyethyl cellulose, 0.4 parts of pH adjuster and 9 parts of water to obtain a nano coating.
[0030] Example 2 S1. Dissolve 0.05 parts of dicyclohexyl phthalate in 50 parts of acetone, add 20 parts of nano-silicon dioxide, stir at 5000 r / min for 30 min, stir at 300 r / min for 20 min, and dry to obtain modified nano-silicon dioxide; S2. Evenly mix 30 parts of pure acrylic emulsion, 10 parts of modified nano silicon dioxide, 2 parts of nano titanium dioxide, 3 parts of nano zinc oxide, 0.5 parts of dispersant, 0.1 parts of wetting agent, 0.2 parts of defoaming agent, 0.3 parts of film-forming aid, 0.2 parts of antifreeze agent, 0.5 parts of hydroxyethyl cellulose, 0.2 parts of pH adjuster and 5 parts of water to obtain a nano coating.
[0031] Example 3 The only difference from Example 1 is: 0.1 part of dicyclohexyl phthalate.
[0032] Example 4 The difference from Example 1 is only that: 1 part of dicyclohexyl phthalate.
[0033] Example 5 The difference from Example 1 is only that: 2 parts of dicyclohexyl phthalate.
[0034] Example 6 The only difference from Example 4 is that one part of dicyclohexyl phthalate is replaced by an equal amount of dicyclohexyl phthalate and 2,5-di-tert-butylhydroquinone in a mass ratio of 1:9.
[0035] Example 7 The only difference from Example 4 is that one part of dicyclohexyl phthalate is replaced by an equal amount of dicyclohexyl phthalate and 2,5-di-tert-butylhydroquinone in a mass ratio of 1:4.
[0036] Example 8 The only difference from Example 4 is that one part of dicyclohexyl phthalate is replaced by an equal amount of dicyclohexyl phthalate and 2,5-di-tert-butylhydroquinone in a mass ratio of 2:3.
[0037] Example 9 The only difference from Example 4 is that one part of dicyclohexyl phthalate is replaced by an equal amount of dicyclohexyl phthalate and 2,5-di-tert-butylhydroquinone in a mass ratio of 4:1.
[0038] Example 10 The only difference from Example 4 is that dicyclohexyl phthalate is replaced by an equal amount of 2,5-di-tert-butylhydroquinone.
[0039] Embodiment 11 The only difference from Example 8 is that 2,5-di-tert-butylhydroquinone is replaced by an equal amount of 4,4'-dihydroxybiphenyl.
[0040] Comparative Example 1 Mix 40 parts of pure acrylic emulsion, 20 parts of nano silicon dioxide, 4 parts of nano titanium dioxide, 6 parts of nano zinc oxide, 1 part of dispersant, 0.3 parts of wetting agent, 0.6 parts of defoaming agent, 0.6 parts of film-forming aid, 0.5 parts of antifreeze agent, 1 part of hydroxyethyl cellulose, 0.4 parts of pH adjuster and 9 parts of water to obtain a nano coating.
[0041] The nano coatings obtained in Examples 1 to 11 and Comparative Example 1 were tested for tensile strength and elongation at break under standard conditions according to the method in JG / T 172-2014. The test results are recorded in Table 1.
[0042] Table 1 Mechanical properties of nano coatings
[0043] It can be seen from Table 1 that the nano coating provided by the present invention has a tensile strength of more than 2.2 MPa and an elongation at break of more than 204%, and has good mechanical properties.
[0044] Compared with Comparative Example 1, Examples 1 to 11 add nano-silica modified with dibasic esters and / or diols, and Comparative Example 1 adds unmodified nano-silica. The tensile strength and elongation at break of the nano-coatings obtained in Examples 1 to 11 are higher than those in Comparative Example 1, indicating that the addition of nano-silica modified with dibasic esters and / or diols can improve the mechanical properties of the nano-coatings.
[0045] The tensile strength and elongation at break of the nano coatings obtained in Examples 3 and 4 are higher than those in Examples 1 and 5, indicating that the mass ratio of the modifier to nano silicon dioxide is 0.1 to 1:20, which can further improve the mechanical properties of the nano coatings.
[0046] The tensile strength and elongation at break of the nano coatings obtained in Examples 6 to 9 are higher than those in Example 4 and Example 10, indicating that the use of dibasic esters and diols in a mass ratio of 1:9 to 4:1 as modifiers can further improve the mechanical properties of the nano coatings.
[0047] The tensile strength and elongation at break of the nano coating obtained in Examples 7 and 8 are higher than those in Examples 6 and 9, indicating that when the mass ratio of dibasic ester to diol is 1:4 to 2:3, the mechanical properties of the nano coating can be further improved.
[0048] The tensile strength and elongation at break of the nano coating obtained in Example 11 are higher than those in Example 8, indicating that 4,4'-dihydroxybiphenyl as a diol can further improve the mechanical properties of the nano coating.
[0049] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A nanometer anti-corrosion and waterproof coating that is resistant to high and low temperatures and acid and alkali, characterized in that: The invention comprises the following raw materials in parts by weight: 30-40 parts of pure acrylic emulsion, 10-20 parts of modified nano silicon dioxide, 2-4 parts of nano titanium dioxide, 3-6 parts of nano zinc oxide, 2-4.4 parts of auxiliary agent and 5-9 parts of water, wherein the modified nano silicon dioxide is nano silicon dioxide modified by a modifier, and the modifier comprises a dibasic ester and / or a diol.
2. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 1 is characterized in that: The mass ratio of the modifier to the nano-silicon dioxide is 0.1 to 1:
20.
3. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 1 is characterized in that: The modifier comprises a dibasic ester and a diol in a mass ratio of 1:9 to 4:
1.
4. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 3 is characterized in that: The modifier comprises a dibasic ester and a diol in a mass ratio of 1:4 to 2:
3.
5. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 4 is characterized in that: The dibasic ester includes dicyclohexyl phthalate.
6. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 4 is characterized in that: The diol includes one or both of 2,5-di-tert-butylhydroquinone and 4,4'-dihydroxybiphenyl.
7. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 1 is characterized in that: The preparation method of the modified nano silicon dioxide comprises the following steps: dissolving a modifier in a solvent, adding the nano silicon dioxide for modification, and drying to obtain the modified nano silicon dioxide.
8. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 7 is characterized in that: The modification includes a first modification and a second modification in sequence, the time of the first modification is 30 to 50 minutes, and the time of the second modification is 20 to 40 minutes; the first modification process is accompanied by high-speed stirring, and the rotation speed of the high-speed stirring is 3000 to 5000 r / min, and the second modification process is accompanied by low-speed stirring, and the rotation speed of the low-speed stirring is 200 to 300 r / min.
9. The nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to claim 7 is characterized in that: The solvent includes one or more of ethanol, acetone and ethyl acetate.
10. A nanometer high and low temperature resistant and acid and alkali resistant anticorrosion and waterproof coating according to any one of claims 1 to 9, characterized in that: The auxiliary agent includes the following components in parts by weight: 0.5-1 part of a dispersant, 0.1-0.3 part of a wetting agent, 0.2-0.6 part of a defoaming agent, 0.3-0.6 part of a film-forming auxiliary agent, 0.2-0.5 part of an antifreeze agent, 0.5-1 part of a thickener, and 0.2-0.4 part of a pH regulator.
Citation Information
Patent Citations
Antiseptic nano crylic acid floor paint
CN106497273A
High-tensile-strength energy-saving waterproof paint and preparation method thereof
CN106590260A
Water-based metallic paint for color plates
CN106833211A
Waterproof coating for wall surface and preparation method thereof
CN108285713A
Aqueous nano hollow glass bead heat-preservation thermal-insulating coating and preparation method thereof
CN110218491A
Cited By
Low-temperature-resistant waterproof coating for outer wall of house building and preparation process of low-temperature-resistant waterproof coating
CN121108835A
Low-temperature-resistant waterproof coating for outer wall of house building and preparation process thereof
CN121108835B